Prehistoric Tower Tombs at Shir/Jaylah, Sultanate of Oman - Yule, Paul A.; Weisgerber, Gerd (Beiträge zur allgemeinen und vergleichenden Archäologie, 1998)
In 1995 survey was undertaken in the Sultanate of Oman in order to monitor the preservation to archaeological monuments. The work centred on over 58 tombs at Shir (Wilīyat Ṣūr). Five types of tombs were discerned. In their form and manner of building the towers the so-called beehive tombs of the Hafit Period, but also share certain resemblances with collective Umm an-Nar period tombs.
Keywords: Archéologie – Oman